(untitled) (Journal of the Management Sciences, 2024)
The increasing incidents of business disruptions and employee hostility has become a major concern for stakeholders, policymakers, investors and academia to adopt socially friendly policies. Adopting socially friendly policies has become a key strategic priority for companies striving for sustainable development in an hostile environment. The study examined the effect of corporate social responsibility disclosure on financial performance of listed multinational firms in Nigeria. This study adopted ex-post facto research design and data were obtained from secondary sources through the annual report of sampled firms and the factbooks of the Nigeria Exchange Group. The population consists of 30 listed multinational firms on the Nigerian Exchange Group as at 31st December, 2023 with a sample size of 15 listed multinational firms were selected using purposive sampling techniques. Data were analyzed using descriptive statistics and panel ordinary least square method. The findings of the study showed that community performance disclosure has positive but insignificant effect on the financial performance as measured by enterprise value of the listed multinational and same goes for leverage. The findings also indicate positive and significant effect of health and safety disclosure, educational sponsorship disclosure on financial performance. The study concluded that health and safety and educational sponsorship disclosure are the most significant variables to inancial performance. It is therefore recommended among others that that management should ensure that the practice of stakeholders’ engagement is explored to improve the community performance of their firms.